First Lie Wins - Elston, Ashley (New York : Pamela Dorman Books/Viking, 2024)
"Evie Porter has everything a nice, Southern girl could want: a perfect, doting boyfriend, a house with a white picket fence and a garden, a fancy group of friends. The only catch: Evie Porter doesn't exist. The identity comes first: Evie Porter. Once she's given a name and location by her mysterious boss Mr. Smith, she learns everything there is to know about the town and the people in it. Then the mark: Ryan Sumner. The last piece of the puzzle is the job. Evie isn't privy to Mr. Smith's real identity,but she knows this job will be different. Ryan has gotten under her skin, and she's starting to envision a different sort of life for herself. But Evie can't make any mistakes--especially after what happened last time. Because the one thing she's worked her entire life to keep clean, the one identity she could always go back to-her real identity-just walked right into this town. Evie Porter must stay one step ahead of her past while making sure there's still a future in front of her. The stakes couldn't be higher--but then, Evie has always liked a challenge.."--.
Reese's Book Club Pick.
New Book Winter 2024.
Keywords: Identity (Psychology) -- Fiction; Novels; Thriller fiction